Malignant catarrhal fever in wild Swedish moose (Alces alces L) - Warame, Ibrahim Yussuf; Steen, Margareta (Rangifer, 1989)
Malignant catarrhal fever (MCF) was diagnosed in two moose (Alces alces L) from the county of Uppland, Sweden. The animals showed an abnormal behaviour e.g. nervous signs as circling movements, nodding of the head and lack of awareness. One of these two animals was shot. The other was found dead on the day after being observed. Gross and histologic findings revealed characteristic lesions of MCF. Serological investigation and viral isolation for BVD and IBR/IPV viruses were negative.